Women's Fertility and Employment Decisions under Two Political Systems - Comparing East and West Germany before Reunification - Julia Bredtmann; Jochen Kluve; Sandra Schaffner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Over the last decades fertility rates have decreased in most developed countries, while female labour force participation has increased strongly over the same time period. To shed light on the relationship between women's fertility and employment decisions, we analyse their transitions to the first, second, and third child as well as their employment discontinuities following childbirth. Using new longitudinal datasets that cover the work and family life of women in the Federal Republic of Germany (FRG) and the German Democratic Republic (GDR) allows for taking into account two political regimes and drawing conclusions about the relevance of institutional factors for fertility and employment decisions. Our results suggest that in both parts of Germany women's probability of having a first child is negatively correlated with both employment and educational achievement. Regarding second and third birth risks, this negative correlation weakens. Analysing women's time spent out of the labour market following childbirth we find that in the East almost all mothers return to work within 18 months after birth. In the West, however, this proportion is much smaller and at the age when the child starts nursery school or school, women re-enter the labour market at higher rates. These results point to a strong influence of institutional circumstances, specifically the extent of public daycare provision. A multivariate analysis reveals a strong correlation between a woman's employment status prior to birth and her probability of re-entering the labour market afterwards.
Keywords: J13; J18; J21; 330; Female labour force participation; fertility; Frauenerwerbstätigkeit; Fruchtbarkeit; Kinderbetreuung; Arbeitsangebot; Berufliche Integration; Vergleich; Systemvergleich; Deutschland; DDR